Effects of different cooking methods of oatmeal on preventing the diet-induced increase of cholesterol level in hypercholesterolemic rats. Issue 1 (December 2015) - Ban, Yandong; Qiu, Ju; Ren, Changzhong; Li, Zaigui
Abstract Background The aim of present study is to investigate the influences of brewing and boiling on hypocholesterolemic effect of oatmeal in rats fed with a hypercholesterolemic diet. Methods Fifty-six male Sprague–Dawley rats were divided into 5 groups of 8 rats each with similar mean body weights and serum cholesterol concentrations. Rats were fed with the experimental diets containing 10 % of oatmeal from two Chinese oat varieties which were brewed or boiled for 30 days. The lipids levels in serum, liver, and faeces were determined. Results The effects of feeding boiled oatmeal on lowering lipid concentrations in plasma and liver were more significant than that of brewed oatmeal (P  < 0.05). Feeding boiled oatmeal was also more efficient in increasing fecal total lipids, cholesterol and bile acids as compared to feeding brewed oatmeal (P  < 0.05). Boiled oatmeal had higher apparent viscosity and soluble β-glucan content than the brewed oatmeal did (P  < 0.05). Conclusion These results indicated that the capability of boiled oatmeal in improving cholesterol metabolism is better than that of brewed oatmeal, which is mainly attributed to its higher soluble β-glucan content and apparent viscosity.